Angiotensin receptor neprilysin inhibitor as a novel antihypertensive drug: Evidence from Asia and around the globe. Issue 3 (11th December 2020) - Lin, Donna S.‐H.; Wang, Tzung‐Dau; Buranakitjaroen, Peera; Chen, Chen‐Huan; Cheng, Hao‐Min; Chia, Yook Chin; Sukonthasarn, Apichard; Tay, Jam Chin; Teo, Boon Wee; Turana, Yuda; Wang, Ji‐Guang; Kario, Kazuomi; et al.
Abstract: Hypertension is a worldwide epidemic that continues to grow, with a subset of patients responding poorly to current treatment available. This is especially relevant in Asia, which constitutes 61% of the global population. Hypertension in Asia is a unique entity that is often salt‐sensitive, nocturnal, and systolic predominant. Sacubitril/valsartan is a first‐in‐class angiotensin receptor neprilysin inhibitor that was first used in heart failure with reduced ejection fraction. Sacubitril inhibits neprilysin, a metallopeptidase that degrades natriuretic peptides (NPs). NPs exert sympatholytic, diuretic, natriuretic, vasodilatory, and insulin‐sensitizing effects mostly via cyclic guanosine monophosphate (cGMP)‐mediated pathways. As an antihypertensive agent, sacubitril/valsartan has outperformed angiotensin II receptor type 1 blockers (ARBs), with additional reductions of office systolic blood pressures ranging between 5 and 7 mmHg, in multiple studies in Asia and around the globe. The drug was well tolerated even in the elderly or those with chronic kidney disease. Its mechanisms of actions are particularly attractive for treatment of hypertension in Asia. Sacubitril/valsartan offers a novel, dual class, single‐molecule property that may be considered as first‐line antihypertensive therapy. Further investigations are needed to validate its safety for long‐term use and to explore other potentials such as in the management of insulin resistance and obesity, which often coexist with hypertension in Asia.